PERBAIKAN PENGENDALIAN PERSEDIAAN MELALUI PERAMALAN PERMINTAAN MENGGUNAKAN METODE TREN ANALISIS - Anita Anita (Asosiasi Dosen Muda Indonesia, 2023)
Forecasting is an activity to predict a value in the future using past data. PT. Daun Biru Engineeringis a company focusing on industry and energy generation maintenance technology. In carrying out its businessactivities, the company has never done quantitative forecasting of future product demand, so the company isnot responsive enough in preparing for production, especially in inventory control which results in expensiveinventory costs. Based on these problems, it is necessary to analyze demand forecasting to improve inventorycontrol using the trend analysis method. There are three trend models used, namely, linear, quadratic andexponential models. The exponential trend model was chosen as the best model, with forecasting results forthe period June - December 2021 including 49, 52, 55, 58, 62, 66 and 70 units. The total estimated inventorycost is Rp. 4,631,873,967.93.